FRI0121 Anti-endothelial cell auto-antibodies and soluble markers of endothelial cell dysfunction in systemic lupus erythemetosus. (1st June 2001) - Dupuy, R; Resplandy, F; Seigneur, M; Schaeverbeke, T; Constans, J; Boisseau, MR; Conri, C
Abstract : Background: In systemic lupus erythematosus (SLE), disease severity may be related to factors such as endothelial cell damage. Objectives: We tested the hypothesis that anti-endothelial cell antibodies (AECA) and plasma markers of endothelial cell dysfunction would be related to disease severity in SLE. Methods: Accordingly we measured AECA by human umbilical vein endothelial cell binding, endothelial markers von Willebrand factor, soluble thrombomodulin, soluble E-selectin by ELISA, and disease severity by SLEDAI and SLICC/ACR in 35 patients with SLE. Results: Despite high levels of IgG AECA (p < 0.001), compared to 21 healthy controls, we found a positive correlation only between IgG AECA and the SLEDAI index (r = 0.393, p = 0.021). We did?t find elevation of soluble markers of endothelial cell dysfunction compared to healthy controls. Conclusion: We conclude that IgG AECA seem to be related to disease activity in SLE, possibly in a pathogenic rôle. Conversely, plasma markers of endothelial cell damage seem to be an epiphenomenon and may only be related to excess inflammation in these patients.